The Impact of Standard Operating Procedures on Lost and Found Unit Officer Services to Garuda Indonesia Airline Passengers at Supadio Pontianak International Airport - Haries Nurcahya; Septiyani Putri Astutik (CV. Rayyan Dwi Bharata, 2023)
Lost and Found is a unit that handles problems with passenger luggage, including loss, damage, and finding of goods with various strategies that will be carried out by lost and found unit officers to gain the trust of passengers who have chosen transportation, so that if luggage damage occurs, the lost and found unit will take care of it. Standard Operating Procedures are a series of instructions used to solve a problem. Therefore, standard operating procedures are very useful for the work of lost and found unit officers to avoid mistakes, delays, obstructions in the process of carrying out their work. This study aims to determine whether there is influence and how much influence standard operating procedures have on the service of lost and found unit officers to Garuda Indonesia airline passengers at Supadio Pontianak International Airport. The research method used in this study is a sequential mixed method with a sequential explonatory type. Data collection techniques in this study used questionnaires, interviews, observation, documentation and research sites at the Lost and Found unit of PT. Gapura Angkasa on the Garuda Indonesia airline at Supadio Pontianak International Airport. The results of the t test show that the independent variable (X) has a significant effect on the dependent variable (Y) with a significant value of 0.000 â‰¤ Î± 0.05, and the results of the coefficient of determination test (R2) show that the magnitude of the effect of the independent variable (X) on the dependent (Y) with the magnitude of the effect reaching 70.4% indicates that standard operating procedures are an important role for lost and found unit officers in serving passengers and 29.6% are influenced by other variables outside of this study.